Climatic and biogeographic processes underlying the diversification of the pantropical flowering plant family Annonaceae - Li, Weixi; Wang, Runxi; Liu, Ming-Fai; Folk, Ryan A.; Xue, Bine; Saunders, Richard M. K. (Frontiers in Plant Science, 2024)
Tropical forests harbor the richest biodiversity among terrestrial ecosystems, but few studies have addressed the underlying processes of species diversification in these ecosystems. We use the pantropical flowering plant family Annonaceae as a study system to investigate how climate and biogeographic events contribute to diversification. A super-matrix phylogeny comprising 835 taxa (34% of Annonaceae species) based on eight chloroplast regions was used in this study. We show that global temperature may better explain the recent rapid diversification in Annonaceae than time and constant models. Accelerated accumulation of niche divergence (around 15 Ma) lags behind the increase of diversification rate (around 25 Ma), reflecting a heterogeneous transition to recent diversity increases. Biogeographic events are related to only two of the five diversification rate shifts detected. Shifts in niche evolution nevertheless appear to be associated with increasingly seasonal environments. Our results do not support the direct correlation of any particular climatic niche shifts or historical biogeographical event with shifts in diversification rate. Instead, we suggest that Annonaceae diversification can lead to later niche divergence as a result of increasing interspecific competition arising from species accumulation. Shifts in niche evolution appear to be associated with increasingly seasonal environments. Our results highlight the complexity of diversification in taxa with long evolutionary histories.